Impact of IT on Transparency, Accountability and Corruption Control in Nepal's Local Governments - Pant, Lalit (SNPRC Journal, 2025)
Information Technology (IT) is essential for improving transparency, accountability, innovation, and national development. This study investigates the impact of IT in selected local bodies for transparency, accountability, and corruption control. The main goal of this study was to evaluate how well local bodies utilize digital infrastructures to enhance governance and service delivery to the public. A mixed-method approach was used, incorporating online surveys and telephone interviews with local government officials and individuals. The findings show that, many local bodies have difficulties when utilizing IT-based system into place, despite increasing awareness of digital governance. Insufficient infrastructure, geographical obstacles, lack of technical expertise and political influence all make it difficult to utilize IT and enhance accountability and transparency in local bodies. As a result, the potential of IT to reduce corruption and strengthen good governance has not yet been completely fulfilled. The study indicates that in order to achieve accountable, transparency, and corruption-free local bodies, it is essential to improve digital infrastructures, strengthen the capacity of local officials, and ensure strong political commitment.